Iron-catalyzed carbonylative cyclization of γ, δ-unsaturated aromatic oxime esters with amines. Issue 93 (5th November 2020) - Zhang, Youcan; Wu, Xiao-Feng
Abstract : An efficient iron-catalyzed carbonylative cyclization of γ, δ-unsaturated aromatic oxime esters with amines has been developed. Abstract : An efficient iron-catalyzed carbonylative cyclization of γ, δ-unsaturated aromatic oxime esters with amines has been developed. A range of functionalized β-homoproline amide derivatives were prepared via an iminyl radical-mediated intramolecular 1, 5-cyclization followed by carbon radical-triggered intermolecular carbonylation. Examples on further transforming the obtained product were successfully discussed as well.